Impact of vaccination on COVID-19 morbidity and mortality among aged people - Priscila Poli; Ana Cristina Ribeiro; Sílvia Carla da Silva André Uehara (Universidade Federal do Ceará, 2024)
Objective: to correlate COVID-19 incidence and mortality rates in elderly people before and after vaccination. Methods: an ecological study with data collected from the official platforms of the State Data Analysis System Foundation and the Prefeitura Municipal de Araraquara (Araraquara City Hall). The data was analyzed using a regression model with a negative binomial distribution and a logarithmic link function. We analyzed 3,188 COVID-19 records in people aged 60 or over, of which 3,137 were eligible for analysis. Results: there was a significant reduction in the incidence of the disease among vaccinated-aged people. No significant differences were observed in the mortality coefficient; however, there was a 67.7% decline in deaths when comparing the periods. Conclusion: the findings indicate a correlation between the vaccination of older individuals and the reduction in COVID-19 incidence and mortality rates, thereby demonstrating and underscoring the significance of adhering to vaccinations. Contributions to practice include the expansion of the theoretical framework regarding the significance of vaccination in reducing morbidity and mortality from COVID-19, particularly in the elderly population. This is especially important considering the endemicity of the disease and the unlimited availability of false information.